Penerapan Media Pembelajaran Komik Digital Story-Based Comics untuk Meningkatkan Minat Belajar Matematika pada Siswa Kelas 2 SDN 056627 Kwala Sawit T.A 2024/2025 - Ginting, Melda Oktika; Silaban, Roikestina (Pusdikra-Publishing.com, 2025)
This research was motivated by the problems that occurred at SDN 056627 kwala Sawit, namely the low interest in learning mathematics of students. This study is aimed at finding out how the Application of Story-Based Comics Digital Comics Learning Media to Increase the Interest in Learning Mathematics of Grade II Students of UPT SDN 056627 Kwala Sawit T.A 2024/2025. The method used in this study is the Classroom Action Research (PTK) method which is carried out in two cycles. Each cycle consists of three meetings. The subjects of this study are 2nd grade students of SD Negeri 064023 Victory Tani T.A 2024/2025 which totals 24 people consisting of 14 girls and 10 boys. The data collection techniques in this study use observation, interview, test and documentation techniques and use qualitative descriptive analysis techniques. Based on the tests that have been carried out in the learning process that it increases in the actions taken in the second cycle, in that cycle the average test results obtained are 78. It can be concluded in this study that in the process of digital comic media story-based comics presented in visual form can attract students' attention. With this, it has a significant impact, namely fostering interest, enthusiasm and focus in mathematics learning activities.